Bacteriophages in Biological Wastewater Treatment Systems: Occurrence, Characterization, and Function - Runa, Viviane; Wenk, Jannis; Bengtsson, Simon; Jones, Brian V.; Lanham, Ana B. (Frontiers in Microbiology, 2021)
Phage bacteria interactions can affect structure, dynamics and function of microbial communities. In the context of biological wastewater treatment (BWT), the presence of bacteriophages can alter the efficiency of the treatment process and influence the quality of the treated effluent. The active role of bacteriophages in BWT has been demonstrated, but many questions remain unanswered regarding the diversity of phages in these engineered environments, the dynamics of infection, the determination of bacterial hosts, and the impact of their activity in full-scale processes. A deeper understanding of the phage ecology in BWT is necessary before improving process monitoring and control, promote higher effluent quality and potentiate the use of phages as biocontrol agents. In this review, we highlight suitable methods for studying phages in wastewater adapted from other research fields, provide a critical overview on the current state of knowledge on the effect of phages on structure and function of BWT bacterial communities, and highlight gaps, opportunities and priority questions to be addressed in future research.